2011
DOI: 10.1093/cid/cir904
|View full text |Cite
|
Sign up to set email alerts
|

Additional Drug Resistance in Mycobacterium tuberculosis Isolates From Resected Cavities Among Patients With Multidrug-Resistant or Extensively Drug-Resistant Pulmonary Tuberculosis

Abstract: The pathogenesis of increasing drug resistance among patients with multidrug-resistant or extensively drug-resistant tuberculosis undergoing treatment is poorly understood. Increasing drug resistance found among Mycobacterium tuberculosis recovered from cavitary isolates compared with paired sputum isolates suggests pulmonary cavities may play a role in the development of worsening tuberculosis drug resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 7 publications
0
51
1
Order By: Relevance
“…Cavitary lesions are heterogeneous and characterized by various levels of fibrosis, necrosis, and vascularization, as demonstrated by the histopathology from our study, and they contain high numbers of M. tuberculosis organisms, many of which reside extracellularly in the caseous center. Clinically, studies have shown the presence of cavitary lesions to be associated with longer time to sputum culture conversion (26), high rates of relapse (27), the development of acquired dug resistance (12,28), and worse treatment outcomes among patients with MDR-TB (29,30). These clinical studies suggest that drug penetration into cavitary lesions may be hindered, possibly due to the physical and functional barriers of cavitary lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cavitary lesions are heterogeneous and characterized by various levels of fibrosis, necrosis, and vascularization, as demonstrated by the histopathology from our study, and they contain high numbers of M. tuberculosis organisms, many of which reside extracellularly in the caseous center. Clinically, studies have shown the presence of cavitary lesions to be associated with longer time to sputum culture conversion (26), high rates of relapse (27), the development of acquired dug resistance (12,28), and worse treatment outcomes among patients with MDR-TB (29,30). These clinical studies suggest that drug penetration into cavitary lesions may be hindered, possibly due to the physical and functional barriers of cavitary lesions.…”
Section: Discussionmentioning
confidence: 99%
“…There is only one published case report evaluating SLD concentrations inside human cavitary lesions (9). Reports of worse clinical outcomes among patients with cavitary disease offer compelling but indirect evidence for low intracavitary SLD concentrations (10)(11)(12).…”
mentioning
confidence: 99%
“…Adjunctive pulmonary resection has been advocated in selected patients with localized MDR-TB and cavitary lesions or a single destroyed lobe [3,22,23,24,25,26,27,28,29,30,31,33]. However, not all patients are suitable candidates, and surgery frequently involves postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical removal of cavities could enhance the sterilizing properties of postsurgical chemotherapy and increase the likelihood of treatment success in these selected patients [24,31,32]. Kempker et al [33] demonstrated that the tuberculous cavity promotes the emergence of increasingly drug-resistant bacilli populations during treatment in M. tuberculosis isolates from resected cavities among patients with MDR and XDR-TB.…”
Section: Introductionmentioning
confidence: 99%
“…To develop new therapeutic approaches, it is critical to understand underlying mechanisms of disease. In pulmonary TB, extracellular matrix (ECM) breakdown causes cavitation and facilitates Mtb transmission (2) and drug resistance (3), and also increases morbidity and mortality (4). Matrix metalloproteinases (MMPs) are zincdependent proteolytic enzymes, which are involved in pulmonary ECM turnover and have diverse immunological roles, such as chemokine processing (5).…”
mentioning
confidence: 99%